Transmission Routes Analysis of SARS-CoV-2: A Systematic Review and Case Report - Li, Huanjie; Wang, Yangyang; Ji, Mingyu; Pei, Fengyan; Zhao, Qianqian; Zhou, Yunying; Hong, Yatian; Han, Shuyi; Wang, Jun; Wang, Qingxi; Li, Qiang; Wang, Yunshan (Frontiers in Cell and Developmental Biology, 2020)
The global outbreak of SARS-CoV-2 spread rapidly throughout the world which transmitted among humans through various routes. Asymptomatic (carriers) and possible fecal-oral transmission, resulted into a large-scale spread. These issues pose great challenges to disease diagnosis and epidemic control. We obtained data on 29 cases of COVID-19 patients in Jinan, China, and reported the clinical data of asymptomatic patients confirmed with stool samples positive. Some patients with gastrointestinal infections are secondary to pulmonary infections, and during the patients' recovery period, the virus may still existin the patient's gastrointestinal tract over 7 days. We combined with epidemiological and clinical data of asymptomatic patients to analyze the possible routes of viral transmission and infection, including eyes-nose, hands-eyes, fecal-oral and eyes-oral, et al., thus first presented the two-way transmission through eyes-oral. Through associating infection symptoms with the transmission routes of virus and the patient course of the disease, we expect to provide guidelines for clinical diagnosis and the basis for suppressing the spread of the virus and antiviral treatment.